Linkage of Tanzania Short Rain Variability to Sea Surface Temperature Over the Southern Oceans - Makula, Exavery Kisesa; Zhou, Botao (Frontiers in Earth Science, 2022)
This study presents the relationship between Tanzania short rain variability and the sea surface temperature (SST) over the Southern Oceans from 1950 to 2017. It is found that the warm SST anomalies over the east of Australia (EA-SST) and the southern Atlantic Ocean (SA-SST) are significantly negatively correlated with the OND throughout Tanzania, signifying that the warmer (cooler) than normal EA-SST and SA-SST tend to cause a suppressed (enhanced) OND rainfall in Tanzania. Further investigation indicates that the above-normal SA-SST anomalies are linked to the changes of Walker-type circulation over the Atlantic Ocean, with the low-level (upper-level) divergence (convergence) occurring over the study region, which suppresses the in-situ convection and hence decreases the rainfall over Tanzania. The above-normal SA-SST anomalies are associated with the upper-level wave patterns propagating from the southern Atlantic Ocean, resulting in the formation of cyclonic anomalies over the target region. The upper-level cyclonic anomalies formed favor the subsidence of airflows over Tanzania and hence reduce rainfall. The local moisture and dynamical conditions also support the atmospheric circulations observed, whereby warm EA-SST and SA-SST anomalies are associated with the westerly moisture flux over the Indian Ocean moving away from Tanzania and the descending motion over Tanzania. Hence, close monitoring of SST anomalies over these regions might be useful in updating OND rainfall seasonal forecasts in Tanzania.